WHOLE PERSON EDUCATION IN EAST ASIAN UNIVERSITIES - Haiyu Zhan (Journal of Dharma, 2024)
Whole Person Education in East Asian Universities: Perspectives from Philosophy and Beyond edited by Benedict S. B. Chan and Victor C. M. Chan, stands as a significant contribution addressing current educational challenges. This volume contains the collective contribution of numerous scholars who participated in the 2019 Conference at Hong Kong Baptist University. Their research aims to integrate contexts for future development through holistic education and philosophy, distinguishing it as a scholarly work rather than a mere textbook. Universities across the world are reconciling differences to enrich higher education by integrating diverse disciplinary perspectives. The book is structured into three Sections. The first Section explores Confucianism, Buddhism, and Chinese perspectives; the second delves into Western philosophy and Asian religions; and the final section examines multidisciplinary and interdisciplinary approaches in philosophy and beyond. Supported by the Tin Ka Ping Foundation and the Centre for Sino-Christian Studies at Hong Kong Baptist University, this research initiative bridges gaps by combining studies on Whole Person Education, East-West Traditions, and Philosophy, aiming to foster comprehensive educational frameworks.